Pengaruh Kedisiplinan Siswa Terhadap Prestasi Belajar Matematika - Umar Wirantasa (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2017)
This study aims to determine the effect of Discipline of Students Against Learning Achievement in Mathematics. The research was conducted in SMP Negeri 223 Jakarta at Jalan Gedong Village Surilang Pasar Rebo Sub-district on June 5, 2012. The method used is a survey method using questionnaire instrument 30 items statements consisting of positive and negative weights. The number of samples taken in this study is numbered 59 respondents from Inroads 235 students, who were taken using simple random sampling technique. Test data analysis requirements are normality test using chi-square test and linearity test using the F test (Fisher), and the results were the normal distribution of data while meeting the linearity test data is linear/significant. Hypothesis test used is a validity test by using product moment and reliability test data using Cronbach Alpha, so the results are utilizable/valid and reliable/feasible to use, valid data of 25 items and invalid data totaling 5. significant regression test that is stated Ho hypothesis is rejected and it can be concluded there is a significant relationship between the discipline of students towards mathematics achievement. From the research that has been done can be concluded that student discipline positive effect on mathematics achievement. Keywords: Student Discipline, Learning Achievement in Mathematics